Connectivity between submerged and near‐sea‐surface coral reefs: can submerged reef populations act as refuges?. Issue 10 (14th August 2015) - Thomas, Christopher J.; Bridge, Tom C.L.; Figueiredo, Joana; Deleersnijder, Eric; Hanert, Emmanuel; Schoeman, David
Abstract Aim Connectivity is a key determinant of coral reef resilience. However, connectivity models rarely account for deep or submerged reefs, despite their widespread occurrence in many coral reef provinces. Here, we model coral larval connectivity among submerged and near‐sea‐surface (NSS) reefs, investigate differences in dispersal potential for coral larvae from these differing reef morphologies and estimate the potential for deeper reef habitats (> 10 m) to provide a source of larvae to shallower reef habitats (< 10 m). Location Great Barrier Reef, Australia. Methods We used two newly developed, high‐resolution models to identify the location and spatial extent of submerged and NSS reefs and to simulate oceanographic currents ('SLIM') affecting larval dispersal. Dispersal patterns for five depth‐generalist coral species with differing life histories and dispersal potential were modelled using an individual‐based model (IBM). Results Near‐sea‐surface reefs were the largest source of larvae successfully settling, but submerged reefs exported a greater proportion of larvae per unit area to other reefs. Larvae originating from submerged reefs also dispersed greater distances. Recruits on shallow‐water reef habitats primarily originated from other shallow areas, but two‐way connectivity did occur between deep and shallow habitats. Empirical data indicate that long‐term coral cover has declined most steeply on the shallow habitats predicted by our model to be highly dependent on other shallow habitats for recruits. Main conclusions Submerged reefs may contribute significantly to larval production and should therefore be considered in connectivity analyses. The hydrodynamic environment on submerged reefs results in larvae dispersing greater distances, potentially increasing their importance as source reefs following disturbances. Deep reef habitats are generally less exposed to disturbances and could therefore constitute an important larval source to some shallow habitats following disturbances. Given the importance of connectivity to coral reef resilience, greater attention should be afforded to identifying and protecting submerged reefs and other deeper habitats.